C-kit+AT2R+ Bone Marrow Mononuclear Cell Subset Is a Superior Subset for Cardiac Protection after Myocardial Infarction. (27th June 2016) - Du, Mingjun; Schmull, Sebastian; Zhang, Wentian; Wang, Chenxi; Lian, Feng; Chen, Yao; Xue, Song
Abstract : Although the bone marrow mononuclear cell (BMMNC) is known as an ideal cell type for cell-based therapy for MI treatment, the effective subpopulation still remains unknown. Our study aimed at identifying the optimal subset of BMMNCs suited for cardiac regeneration. In this study, we observed that MI led to (i) a significant increase of the c-kit + AT2 R + BMMNC subpopulation in mice and (ii) a modest increase of AT2 R + BMMNCs in humans. c-kit + AT2 R + and c-kit + AT2 R − BMMNC subpopulations were obtained from mice after MI. Then, we cocultured cardiac H9C2 cells with c-kit + AT2 R +, c-kit + AT2 R −, and unfractionated BMMNCs; finally, we found that the c-kit + AT2 R + subset is superior to the c-kit + AT2 R − subset in improving cardiomyocyte protection in vitro. Of note, c-kit + AT2 R + BMMNCs showed a more robust migration capacity than c-kit + AT2 R − and unfractionated BMMNCs in vitro and in vivo . Additionally, compared to c-kit + AT2 R − and unfractionated BMMNCs, intravenous transplantation of c-kit + AT2 R + BMMNC resulted in smaller infarct size and lower levels of inflammatory reactions in heart tissue, leading to a higher global heart function improvement. In conclusion, our results indicate that the c-kit + AT2 R + BMMNC subpopulation exerts a protective effect against MI and shows promising therapeutic possibilities with regard to the treatment of ischemic heart disease.